2022
DOI: 10.1002/aesr.202200010
|View full text |Cite
|
Sign up to set email alerts
|

MOF‐derived Multi‐Shelled NiP2 Microspheres as High‐Performance Anode Materials for Sodium‐/Potassium‐Ion Batteries

Abstract: With the booming of renewable energy sources and the extensive promotion of large-scale energy storage devices, sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs) exhibit the potential to share the pressure on expensive lithium-ion batteries (LIBs) in energy storage field. [1][2][3][4][5] The fascinating advantages of SIBs and PIBs include abundance of sodium and potassium resources, cost effectiveness, superior safety properties, and similar operating mechanism with LIBs. [6][7][8][9][10][11][12] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…This confirms that there are strong interactions in dual heterogeneous interfaces of MoO 2 /MoS 2 /C. [ 27,28 ] According to the thermogravimetric analyzer (TGA) and inductively‐coupled plasma (ICP) spectroscopy, the contents of MoO 2 , MoS 2 and C in dual heterojunction interface MoO 2 /MoS 2 /C are ≈33%, 27%, and 40%, respectively, while the percentages of MoO 2 , MoS 2 and C in MoO 2 /C and MoS 2 /C are 44% /56% and 53%/47%, respectively (Figure 2b; Figure S8, Supporting Information). To obtain more information about the chemical environment in dual heterojunction interface MoO 2 /MoS 2 /C, X‐ray photoelectron spectroscopy (XPS) characterizations were carried out (Figure S9, Supporting Information).…”
Section: Resultssupporting
confidence: 69%
“…This confirms that there are strong interactions in dual heterogeneous interfaces of MoO 2 /MoS 2 /C. [ 27,28 ] According to the thermogravimetric analyzer (TGA) and inductively‐coupled plasma (ICP) spectroscopy, the contents of MoO 2 , MoS 2 and C in dual heterojunction interface MoO 2 /MoS 2 /C are ≈33%, 27%, and 40%, respectively, while the percentages of MoO 2 , MoS 2 and C in MoO 2 /C and MoS 2 /C are 44% /56% and 53%/47%, respectively (Figure 2b; Figure S8, Supporting Information). To obtain more information about the chemical environment in dual heterojunction interface MoO 2 /MoS 2 /C, X‐ray photoelectron spectroscopy (XPS) characterizations were carried out (Figure S9, Supporting Information).…”
Section: Resultssupporting
confidence: 69%
“…(e), Ni2+ species and Ni metal/NiN x are present in all Co x Ni y /NC catalysts[39][40][41]. For Co doped samples, appropriate amount of Ni elements can increase the content of CoN x species which also applicable to the Ni doped samples.…”
mentioning
confidence: 98%
“…[113,114] Among these methods, solution-based reactions show better environmental benignity and higher economic efficiency, while solid-state conversion warrants the crystallinity degree of products. The solid-state conversion route has been the predominant protocol in MOF-derived phosphate preparation, during which direct phosphorization [115,116] and multi-step thermal treatment [117,118] are viable. During the phosphorization procedure, red phosphorus and NaH 2 PO 2 are prevailing exterior P sources that can ensure the successful synthesis of phosphides.…”
Section: Synthesis Strategies For Mof-based Sib Electrodesmentioning
confidence: 99%
“…Li et al reported the synthesis of NiP 2 nanoparticles loaded in multishelled hollow N-doped carbon (NiP 2 @MHNC) microspheres using Ni-BTC MOF via annealing and phosphorization. [118] The title electrode proceeds with a conversion reaction mechanism for sodium ion storage with the advantages of synergy of heterogeneous interface, N-doped carbon, and multi-shelled hollow structure. A microporous structure of ZIF-67-derived Ni 2 P polyhedron particles embedding in highly rough carbon fibers (denoted as Ni 2 P@C-N⊂CF) was reported as SIB anode material by Wang and group.…”
Section: Mof-derived Metal Phosphidesmentioning
confidence: 99%